2013 3rd International Conference on Instrumentation Control and Automation (ICA) 2013
DOI: 10.1109/ica.2013.6734042
|View full text |Cite
|
Sign up to set email alerts
|

P300 detection based on extraction and classification in online BCI

Abstract: In this paper, an application of nonlinear principal component analysis for online P300 extraction and classification is proposed. In order to cover the nonlinearity between the variables, a five-layer neural network is applied for feature extraction. The experimental results in this work show that the implementation of the proposed method achieves a very significant statistical improvement in extracting and classifying P300 components. After a short time of practice, most participants could learn to extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hutagalung and Munandar worked on an online data using nonlinear principal component analysis (NPCA) as a feature extraction method and backpropagation neural networks as a classification method without any of the down-sampling or averaging preprocessing steps [35].…”
Section: Other Approaches For P300 Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hutagalung and Munandar worked on an online data using nonlinear principal component analysis (NPCA) as a feature extraction method and backpropagation neural networks as a classification method without any of the down-sampling or averaging preprocessing steps [35].…”
Section: Other Approaches For P300 Classificationmentioning
confidence: 99%
“…If only a single trial is used, the classification accuracy is 60% using the approach that had been implemented by Hutagalung and Munandar [35] and the classification accuracy is equal to or less than 30% for the other two approaches [12] [36]. Nearest training subspace can be found using the smaller value of the calculated principal angles.…”
Section: Other Approaches For P300 Classificationmentioning
confidence: 99%
“…[ 4 5 ] Artificial intelligence methods have been proposed to increase SNR without loss of any considerable information in P300 detection. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] One of the most important techniques to detect P300 is artificial neural network. [ 6 15 16 ] Although usefulness of this idea, its basic drawback is getting stuck in local minimum which degrades its performance in P300 detection. In recent years, studies have demonstrated the potential of deep neural networks in the field of P300 detection.…”
Section: Introductionmentioning
confidence: 99%